Peningkatan Pengetahuan Masyarakat Dalam Penanganan Asma Bronchiale Kelurahan Labuhan Deli - Nixson Manurung (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
TB is one of the 10 causes of death and the primary cause of infectious agents in the world. The prevalence of tuberculosis patients in 2020 amounted to 929 patients. Some influencing factors are behavioral factors, namely knowledge, attitudes and behavior in the implementation of routine treatment compliance. The method used was descriptive observational with 30 participants who were residents of Sampali Village, Percut Sei Tuan District. The PkM team provided material that meant 1) Definition of tuberculosis disease, 2) Causes of tuberculosis disease 3) Signs and symptoms of tuberculosis disease, 4) Complications of tuberculosis disease, and 5) Prevention of tuberculosis disease. After the implementation of the activity: 1) The definition of tuberculosis (TB) is mostly good as many as 25 people, 2) The causes of tuberculosis (TB) were mostly good as many as 27 people, 3) Signs and symptoms of tuberculosis (TB) were mostly good as many as 26 people, 4) Complications of tuberculosis (TB) were mostly good as many as 27 people, and 5) Prevention of correct transmission of tuberculosis (TB) all participants were able to 27 people. The increase in knowledge and skills of participants is due to the community's great desire to treat and prevent dengue fever in family members at home.